THEORETICAL AND METHODOLOGICAL BASES OF TECHNOLOGIES OF FORMATION OF COMMUNICATIVE CULTURE OF TEACHERS-TO-BE - Oliiar, Mariia (Mountain School of Ukrainian Carpaty, 2019)
The training of modern highly qualified specialists in the field of education should be in line with international standards. Modernization of education is impossible without achieving a proper level of communicative culture of teachers. However, the problem of development of modern technologies for the formation of communicative culture of teachers-to-be is not fully explored in scientific research works. The purpose and objectives of this article is to reveal the theoretical and methodological foundations of technologies for the formation of communicative culture of teachers-to-be. The research of communicative culture of students has demonstrated that it is necessary to make adjustments in the educational process of higher educational institutions. The communicative culture of the teacher is a system-integrative quality that facilitates a successful interaction between a teacher and a student in the system of subject-to-subject relations. The technology of formation of communicative culture of teachers-to-be is a summation of content, methods, forms and means, as well as the system of actions of educational process subjects. It involves several consecutive stages: the stage of future communication design, the stage of its implementation, and the diagnostic and correctional stage. Communicative situations are the main technological element. The dialogue is a key element of educational communicative situations. The technology of formation of communicative culture develops the ability of teachers-to-be to build a constructive dialogue. It helps future specialists to develop such personal qualities as creativity, independence, activity, and reflection.